2000
DOI: 10.1021/jo0003347
|View full text |Cite
|
Sign up to set email alerts
|

Alkyl- and Arylthiodediazoniations of Dry Arenediazoniumo-Benzenedisulfonimides. Efficient and Safe Modifications of the Stadler and Ziegler Reactions to Prepare Alkyl Aryl and Diaryl Sulfides

Abstract: The reaction between dry arenediazonium o-benzenedisulfonimides 1 and sodium thiolates in anhydrous methanol represents an efficient and safe procedure, of general validity, for the preparation of unfunctionalized or variously functionalized alkyl aryl and diaryl sulfides. As a rule, the reaction temperature was maintained at 0-5 degrees C for the alkylthiodediazoniations and at room temperature (20-25 degrees C) for the arylthiodediazoniations. The sulfide yields are generally high; of the 63 considered examp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…(Table 3, entry 1): [33] 100 mL of stock solution A were used; column chromatography: hexane/ethyl acetate 50:1; colorless liquid (98 % yield). Octyl phenyl sulfide (Table 3, entry 2): [44] 100 mL of stock solution A were used; column chromatography: hexane; colorless liquid (91 % yield). Octyl phenyl sulfide (Table 3, entry 3): 50 mL of stock solution A were used; colorless liquid (91 % yield).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Table 3, entry 1): [33] 100 mL of stock solution A were used; column chromatography: hexane/ethyl acetate 50:1; colorless liquid (98 % yield). Octyl phenyl sulfide (Table 3, entry 2): [44] 100 mL of stock solution A were used; column chromatography: hexane; colorless liquid (91 % yield). Octyl phenyl sulfide (Table 3, entry 3): 50 mL of stock solution A were used; colorless liquid (91 % yield).…”
Section: Methodsmentioning
confidence: 99%
“…(Table 3, entry 8): A solution of PdA C H T U N G T R E N N U N G (OAc) 2 (4.4 mg) and CyPF-tBu (11 mg) in DME (1 mL) was used as catalyst; the reaction was conducted at 70 8C; 97 % yield. (Table 3, entry 9): [45] (Table 3, entry 10): [44] 50 mL of stock solution A were used; column chromatography: hexane; colorless liquid (91 % yield). 4 mg) and CyPF-tBu (11 mg) in DME (1 mL) was used as catalyst; the reaction was conducted at 70 8C; 89 % yield.…”
Section: -Methoxyphenyl Octyl Sulfidementioning
confidence: 99%
“…A recent comprehensive report, in a modified Ziegler reaction, has employed stable and safe arenediazonium o-benzenesulfonimides for the preparation of a large number of alkyl aryl and diaryl sulfides using a number of aliphatic and aromatic thiolates under basic conditions. 7 The stability of arenediazonium tetrafluoroborates makes them attractive arylating agents, they are also easily prepared and stored. 8 Keumi et al 9 have reported that arenediazonium tetrafluoroborates could be readily dediazoniated with trimethylsilyl derivatives such as TMSCl, TMSBr, TMSI and TMSN 3 in dimethylformamide upon warming or at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…3 In this procedure [ 18 F]4-fluorophenylalanine (3) was obtained and diazotized in high yield, as shown by monitor reactions. Although diazothio-compounds are note suitable for a direct introduction of 18 F into an aromatic ring, the high reactivity of the sulfhydryl-group of cysteine with diazonium ions to form diazothio-compounds 4,5 and arylthioethers by thiodediazonation [6][7][8] may provide a possible reaction pathway for the synthesis of radiopharmaceuticals containing the 18 Faryl thioether moiety. In this paper, we describe an adaptation of the synthesis of the diazonium ion 4 and its application to the synthesis of 18 F-labeled 7 ( Figure 2).…”
Section: Introductionmentioning
confidence: 99%